The Influence of CSR and Ethical Self-Identity in Consumer Evaluation of Cobrands - Singh, Jaywant (Journal of business ethics, 2016)
An important aspect of brand perception emanates from its corporate social responsibility (CSR) activity. When two brands involved in CSR activities form a cobranding alliance, their respective CSR perceptions can impact consumer attitudes toward the alliance. As an ethically-oriented strategy, the alliance can be potentially beneficial to both partner brands, and can create opportunities for promoting CSR activities. The research streams on brand management, cobranding, and CSR, however, are silent about this important branding strategy that has several embedded business and societal benefits. This study examines how CSR-based consumer perceptions and ethical self-identity impact consumer evaluation of cobrands. Employing a quasi-experimental between-subjects design, the study tests six cobranding scenarios in three product categories. The data were collected via structured questionnaires resulting in 318 valid responses. The data were analyzed employing Partial Least Squares Structural Equation Modeling. The results confirm that positive CSR perceptions toward the partner brands are robust indicators of attitudes toward cobrands. Further, the match between the CSR activities of the partner brands (positive CSR fit) and the product categories (product fit) influences cobrand attitudes. The results also show evidence of ‘spill-over’ effects, where the alliance has a positive impact on subsequent CSR perceptions toward the partner brands. Additionally, the findings demonstrate an asymmetry in the effects of the cobrand on subsequent CSR perceptions wherein consumers with low ethical self-identity show greater spill-over effects from the cobrand than those with high ethical self-identity. The study contributes to knowledge in the domains of business ethics, cobranding, and social responsibility. The findings have managerial implications for designing CSR-based ethical branding strategies for cobrands.